Novel anti-GARP antibody DS-1055a augments anti-tumor immunity by depleting highly suppressive GARP+ regulatory T cells. (3rd June 2021) - Satoh, Kazuki; Kobayashi, Yoichi; Fujimaki, Kaori; Hayashi, Shinko; Ishida, Saori; Sugiyama, Daisuke; Sato, Takahiko; Lim, Kyungtaek; Miyamoto, Megumi; Kozuma, Shiho; Kadokura, Michinori; Wakita, Kenichi; et al.
Abstract: Regulatory T (Treg) cells, which are essential for maintaining self-tolerance, inhibit anti-tumor immunity, consequently hindering protective cancer immunosurveillance, and hampering effective anti-tumor immune responses in tumor-bearing hosts. Here, we show that depletion of Treg cells via targeting glycoprotein A repetitions predominant (GARP) induces effective anti-tumor immune responses. GARP was specifically expressed by highly suppressive Treg cells in the tumor microenvironment (TME) of multiple cancer types in humans. In the periphery, GARP was selectively induced in Treg cells, but not in effector T cells, by polyclonal stimulation. DS-1055a, a novel afucosylated anti-human GARP monoclonal antibody, efficiently depleted GARP + Treg cells, leading to the activation of effector T cells. Moreover, DS-1055a decreased FoxP3 + CD4 + T cells in the TME and exhibited remarkable anti-tumor activity in humanized mice bearing HT-29 tumors. We propose that DS-1055a is a new Treg-cell-targeted cancer immunotherapy agent with augmentation of anti-tumor immunity. Abstract : A new anti-GARP antibody that enhances antitumor immunity